Improving intercultural interactions modules for cross-cultural training programs. Vol. 1 - Cushner, Kenneth; Brislin, Richard W., 1945-; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1994)
This volume addresses new topics specific to various types of intercultural experience including ethics, ethnocultural identification, conflict and mediation across cultures, empathy and cross-cultural communication.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Intercultural communication; Cross-cultural orientation; Multicultural education; Electronic books